Conscientiousness and attitude towards the thesis in university students of a scientific society - Mamani-Benito, Oscar Javier (2019)
In order to determine if the Conscientiousness trait of personality is a good predictor of the attitude towards the thesis, a predictive correlative study was carried out with a population of 83 university students of a Scientific Society. The conscientiousness sub-scale of the NEO PI-R personality inventory and the attitude scale towards the realization of a thesis were applied. The results show that the facets of competence, sense of duty and reflection are what significantly predict the attitude towards the university thesis; likewise, a direct and moderate association is observed between both variables. The predominance of the conscientiousness trait in the personality profile of university students involved in research groups predicts favorable attitudes towards the elaboration of degree work.